Microstructure and Mechanical Property of Hot-Pressed Al2O3-Ni-P Composites Using Ni-P-Coated Al2O3 Powders - Hyeong-Chul Kim; Jae-Kil Han (Advances in Materials Science and Engineering)
Al2O3-Ni-P composite powders with Ni-P contents of 10.9, 14.4, and 20.4 wt.% were synthesized via the Ni-P electroless deposition process. The as-received Al2O3-Ni-P composite powders were composed of Ni-P particles and Ni-P coating layer. Some Ni-P particles randomly adhered to the Al2O3 powders, and their particle diameter ranged from 5 nm to 20 nm. The thin Ni-P layer had about 5 nm thick amorphous structure and directly bonded with Al2O3 powders. Using the Ni-P-coated Al2O3 powders, a dense Al2O3-Ni-P composite can be successfully obtained using the hot press process at 1,350°C for 1 hour in an Ar atmosphere under an applied pressure of 30 MPa. The hot-pressed Al2O3-15 wt.% Ni-P composite showed excellent material properties. Its relative density, Vickers hardness, and fracture toughness were comparatively high: about 99.1%, 2,360 Hv, and 6 MPa·m1/2, respectively. The fracture surface of the hot-pressed Al2O3-Ni-P composite showed a semiductile mode due to the mixed intergranular and transgranular fracture mode. In particular, the fracture toughness of the hot-pressed Al2O3-15 wt.% Ni-P composite was strongly enhanced by the combined action of the crack branching and the crack deflection.